Social networks usage in the strengthening of reading competences - Angela Consuelo Rodríguez Gaitán; Aída Yamile Pachón Fernández (GACETA DE PEDAGOGÍA, 2024)
The inclusion of ICT in education is considered a skill that strengthens the development of reading skills, but some institutions do not consider the management of social networks relevant as a learning strategy. This article aims to determine the importance of managing a Didactic Sequence (SD) using the social network Ed mode. At the methodological level, a descriptive study with a mixed approach was used, applying the survey to students and teachers to know habits of ICT use, as a result, some findings were found that were categorized based on the exercises applied, making known the importance of using social networks as a learning medium to improve reading skills. To conclude, it was determined that the use of social networks and web 2.0 tools are a fundamental axis for the development of collaborative work, linking digital tools.